The Effect of Brand Image, Cost, And Service Quality on Loyalty Through Patient Satisfaction at the Pa Clinic in West Bandung Regency - Novia Ayu Wijayantis Susanto Putri; A. Rohendi; Yani Restiani Widjaja (Research of Service Administration Health and Sains Healthys, 2025)
This study aims to analyze the influence of brand image, cost, and service quality on patient loyalty through patient satisfaction at the PA Clinic in West Bandung Regency. The method used is a quantitative approach with a survey of clinic patients, where data is collected through a questionnaire that measures patients' perceptions of brand image, cost, service quality, satisfaction, and loyalty. The analysis was conducted to determine the direct and indirect relationships among the variables, with patient satisfaction as the mediating variable. The results of the study indicate that brand image, cost, and service quality significantly influence patient satisfaction. A strong brand image creates trust and positive perceptions, while appropriate costs enhance the attractiveness of services without compromising quality. Service quality, which includes the reliability of medical staff, punctuality, facility comfort, and staff friendliness, is a dominant factor in shaping patient satisfaction. Patient satisfaction was found to be an important mediator in enhancing loyalty; satisfied patients are more likely to continue using the clinic's services and recommend them to others, even though there are many alternative healthcare facilities in the study area. These findings underscore the need for an integrated strategy to strengthen brand image, align costs with patients' purchasing power, and maintain high service standards to retain and enhance patient loyalty amid intense competition among clinics.